Pengembangan Virtual Laboratory Termodinamika di Sekolah Menengah Atas - Elce Purwandari (SPEJ (Science and Physic Education Journal), 2019)
This study aims to produce virtual laboratory thermodinamic that is valid, practical, and effective used in learning physics at SMAN 2 Palembang. Using development research methods the Hannafin and Peck model which consist of three phases, namely analysis phases, design phases, and development and implementation phases. At the development and implementation phases of evaluation method of Tessmer. Virtual laboratory are declared valid after an evaluation by an expert review. Virtual laboratory is then evaluated by students in the phase of one-to-one and small group and is declared very practical to use. The results of data analysis of Learning motivation of the students increase an average from 0,69 become 0,8, learning outcomes of the students increase an averag from 43,13 become 76,13. The results of N-gain analysis show an 0,58 with a medium category. It was concluded that virtual laboratory thermodynamic it has been developed was proven to be valid, practical, and effective.This shows that virtual laboratory thermodynamic can be developed, practical to used, and increases motivation and student cognitive learning outcomes. Keywords:Virtual Laboratory, Thermodynamics, Valid, Practical, and Effective